Potensi artificial intelligence dalam menggantikan peran akuntan di masa depan - Hasanah, Nabila Ikfi (Maliki Interdisciplinary Journal, 2026)
The rapid development of Artificial Intelligence (AI) has brought fundamental transformations to the field of management accounting, sparking discussions regarding the potential shift and replacement of accounting roles through automation in the future. This study aims to analyze the implications of AI on the accounting profession and the accompanying ethical challenges. Employing a qualitative descriptive method through a literature review, this research explores how AI is reshaping job structures and ethical practices within accounting. The findings indicate that while AI offers high efficiency, rigorous system standardization is required to ensure quality, accuracy, and compliance with accounting principles. This study emphasizes the importance of collaboration between ethics experts and accounting practitioners in technological development to ensure that AI-generated decisions remain aligned with moral values. Furthermore, the research highlights the necessity of enhancing accountant competencies to bridge the technological gap. In conclusion, adaptability and a strengthened understanding of ethics are key for accounting professionals to remain relevant and to integrate AI as a supporting tool rather than a mere replacement for human roles.